Comparison of the implementation Cooperative Learning Model Team Assisted Individualization (TAI) and Time Token Types on the Completion of Learning Outcomes in Volleyball overhead Pass - Nugroho, Mahir Dwi; Putra, Fadli Suardhana Eka; Munawar, Sayyid Agil Rifqi (International Journal of Education, Information Technology, and Others, 2025)
Cooperative Learning has quite high effectiveness in improving learning completion, but is not specific because there are many types of Cooperative Learning. This study aims to determine the effectiveness of cooperative learning in physical education subjects on Volleyball overhead passing material for class VII students at SMPN 42 Surabaya. The cooperative model chosen is the Time Token and Team Assisted Individualization (TAI) types because they are relevant to the potential of students in that class. The research method used is experimental research with a quantitative descriptive approach. The sample in this study amounted to 80 students, consisting of 40 students in class VII-F as the X1 TAI experimental group and 40 students in class VII-E as the X2 Time Token experimental group. From the calculation of the independent t test, it can be concluded that there is no difference between the TAI and Time Token models on the completion of volleyball overhead passing learning outcomes as evidenced by the t count value = 1.66 which is smaller than t table (1.66 <1.99). The cooperative learning model that has a greater influence on the completion of volleyball overhead passing learning outcomes in class VII students of SMP Negeri 42 Surabaya is the TAI type with a large increase of 0.376% in the skill aspect. The TAI type is recommended for Physical Education learning, of course with systematic class management in order to get optimal results